Cabaran menyesuaikan diri sebagai ibu muda dalam kalangan remaja hamil luar nikah: satu kajian kualitatif - Salina Nen,; Farah Hidayah Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The pregnancy rate among Malaysian adolescents is alarming. Most pregnancy among adolescents appears to be unplanned and/or unwanted. Adolescent pregnancy usually occur outside marriage, thus is often suffered from social stigma and discrimination. A teen pregnancy is usually difficult for teenage mother to adapt and cope due to many problems. The study aimed to explore the experiences of pregnancy and motherhood among unwed adolescents’ mothers during pregnancy and after newborns. This study used a qualitative approach. A case study was selected to describe the essence of a phenomenon. Meanwhile, the semi-structured interview was used as a method to obtain the data. Purposive sampling with predetermined criteria was used to select potential participants. A total of five pregnant adolescents from the shelter home services for unwed teenage mothers were agreed to participate in the study. The study found that these young mothers experiences a lot of challenging issues associated with their unplanned or unwanted pregnancy including family crisis, psychological stress, financial difficulties, academics disturbance and harassment from ex-boyfriends. This study provides insight into the pressure and challenges facing by adolescents’ mother in order to adapt with their current condition. Discussion about the need for better support and empowerment are also highlighted.